Asthma in COVID-19: Mitigating or exacerbating? An interesting case report. (June 2022) - Al Amin, A.S.M.; Ataullah, A.H.M.; Rahman, Abdur; Uddin, Md. Shalah; Nahar, Sabekun; Rahman, Md Moshiur; Sarwar, A.S.M.; Lozada-Martinez, Ivan David; Rahman, Sabrina
Abstract: Introduction: Bronchial asthma is an age-old disease whereas COVID-19 is an officially declared pandemic on March 11, 2020 by WHO. Since both are primarily a disease of the respiratory system, researchers across the globe tried to explore the potential relationship between them; to date, there is no convincing data. Here, we tried to present a case to explore potential relationships between these two, if present. Case presentation: A 30-year-old male patient with well-controlled cough variant asthma was diagnosed with a case of covid-19 infection 12 months back. All other sign symptoms subsided except dry cough. The patient is treated with an inhaled bronchodilator, oral and inhaled steroid, Tab montelukast as well as other conservative management like hot water vapor, lozenge, honey, etc but symptoms were not controlled for the last 12 months. The patient could not do his job because of this problem. All examination and investigation findings were normal. After long-term use of inhaled steroids, he is now 50–60% improved and gradually improving. Discussion: Covid can exacerbate cough in an asthmatic patient. Neuronal activation and neuroinflammatory mechanisms may aggravate this cough after covid. Diagnosis confirmed clinically with the relevant improvement of symptoms. Other important differentials were excluded by appropriate history, examinations, and investigation. Cough is improved by steroids in this case. Conclusion: Summary of conclusion: Cough variant asthma may be aggravated with covid 19 infection and meticulous history, treatment, and follow up needed for an asthmatic patient who is infected with covid 19. Highlights: Bronchial asthma is an age-old disease whereas COVID-19 is an officially declared pandemic by WHO. COVID-19 can exacerbate cough in an asthmatic patient. History, treatment, and follow up needed for an asthmatic patient infected with COVID-19.